Design and Performance Analysis of 6T SRAM cell on 90nm technology - Zargar, Mehak; Goel, Anuj Kumar (2023 4th IEEE Global Conference for Advancement in Technology (GCAT), 2023)
Due to its substantial storage capacity and rapid access times, SRAM has emerged as a key element in many VLSI Chips. The quick development of low-voltage, low-power devices memory design over the past few years due to the surge in demand for notebooks and laptops has made SRAM the subject of extensive research devices for communication and IC memory. Due to its availability and minimal standby leakage, SRAMs are frequently employed for on- and off chip memories in mobile and computer applications. The primary goal in this work is to evaluate performance at of 6T SRAM cells at 90nm technology in terms of parameters like CR, PR read-delay writ- delay Read- power, Write- power and RSNM.